Implementasi Konsep Ta’dib dalam Pendidikan Islam Membentuk Santri Berkarakter - Rahman, Abdur; Subando, Joko (Lembaga Yasin AlSys, 2025)
The concept of education, whether formal, informal, or non-formal, in the perspective of Islamic education, is fundamentally aimed not only at equipping students with knowledge and skills but also at fostering emotional, social, and spiritual intelligence. This approach is intended to shape them into individuals with the character of insān kāmil (a complete and noble human being). In relation to this, the philosophy of Islamic education encompasses the terms tarbiyah, ta'lim, and ta'dib. Among these, the term ta'dib is considered the most appropriate, as it encompasses not only the transfer of knowledge but also the transfer of values to students.